RNAi-mediated gene knockdown of progesterone 5β-reductases in Digitalis lanata reduces 5β-cardenolide content - Klein, Jan; Horn, Elisa; Ernst, Mona; Leykauf, Tim; Leupold, Tamara; Dorfner, Maja; Wolf, Laura-Sophie; Ignatova, Anastasiia; Kreis, Wolfgang; Munkert, Jennifer (Plant Cell Reports, 2021)
Key message: Studying RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of Digitalis lanata, we here provide direct evidence for the participation of PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) in 5β-cardenolide formation. Abstract: Progesterone 5β-reductases (P5βR) are assumed to catalyze the reduction of progesterone to 5β-pregnane-3,20-dione, which is a crucial step in the biosynthesis of the 5β-cardenolides. P5βRs are encoded by VEP1-like genes occurring ubiquitously in embryophytes. P5βRs are substrate-promiscuous enone-1,4-reductases recently termed PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes). Two PRISE genes, termed DlP5βR1 (AY585867.1) and DlP5βR2 (HM210089.1) were isolated from Digitalis lanata. To give experimental evidence for the participation of PRISEs in 5β-cardenolide formation, we here established several RNAi-mediated DlP5βR1 and DlP5βR2 knockdown shoot culture lines of D. lanata. Cardenolide contents were lower in D. lanata P5βR-RNAi lines than in wild-type shoots. We considered that the gene knockdowns may have had pleiotropic effects such as an increase in glutathione (GSH) which is known to inhibit cardenolide formation. GSH levels and expression of glutathione reductase (GR) were measured. Both were higher in the Dl P5βR-RNAi lines than in the wild-type shoots. Cardenolide biosynthesis was restored by buthionine sulfoximine (BSO) treatment in Dl P5βR2-RNAi lines but not in Dl P5βR1-RNAi lines. Since progesterone is a precursor of cardenolides but can also act as a reactive electrophile species (RES), we here discriminated between these by comparing the effects of progesterone and methyl vinyl ketone, a small RES but not a precursor of cardenolides. To the best of our knowledge, we here demonstrated for the first time that P5βR1 is involved in cardenolide formation. We also provide further evidence that PRISEs are also important for plants dealing with stress by detoxifying reactive electrophile species (RES).
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cardenolide biosynthesis; Digitalis lanata; Glutathione; Progesterone 5β-reductases (P5βR); Reactive electrophile species; RNAi-mediated knockdown

RNAi mediated knock down of 3 beta-hydroxysteroid dehydrogenases in Digitalis lanata shoot cultures - Leykauf, Tim; Klein, Jan; Ernst, Mathias; Kreis, Wolfgang; Munkert, Jennifer (PLANTA MEDICA, 2019)
CRIS-Team WoS Importer:2020-01-10